2009
DOI: 10.1007/dcr.0b013e31819ad4f2
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes for Patients Developing Anastomotic Leak After Ileal Pouch-Anal Anastomosis

Abstract: Outcomes including functional results and pouch failure rates for patients developing a leak after stapled anastomosis at ileal pouch-anal anastomosis were significantly better than outcomes for patients who develop a leak after handsewn anastomosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Although preservation of the ATZ purportedly improves functional results, [16][17][18][19] shortens operative times, 20 and reduces septic complications, 21,22 considerable controversy still exists regarding long-term outcomes as a result of recurrent or persistent disease and the risk of malignant degeneration in the ATZ. In sharp contrast, surgeons who advocate mucosal proctectomy, as we do at our center, emphasize that the complete removal of all rectal mucosa not only confers the highest likelihood of a complete surgical cure but more importantly removes all future risk of malignant transformation.…”
Section: Mucosectomy With Handsewn Versus Double-stapled Anastomosismentioning
confidence: 99%
“…Although preservation of the ATZ purportedly improves functional results, [16][17][18][19] shortens operative times, 20 and reduces septic complications, 21,22 considerable controversy still exists regarding long-term outcomes as a result of recurrent or persistent disease and the risk of malignant degeneration in the ATZ. In sharp contrast, surgeons who advocate mucosal proctectomy, as we do at our center, emphasize that the complete removal of all rectal mucosa not only confers the highest likelihood of a complete surgical cure but more importantly removes all future risk of malignant transformation.…”
Section: Mucosectomy With Handsewn Versus Double-stapled Anastomosismentioning
confidence: 99%
“…This is much lower than the rate of pouch-anal anastomotic leaks that occured in 5% (177/3542) of our own IPAAs during the past 25 years. 14 Although pouch leak rates fortunately remain low, they may occur more frequently in the setting of redo pouch surgery. During the same queried period, we performed a total of 410 redo pouch procedures, of which 66 (16.1%) had leaks from the tip of the J-pouch.…”
Section: Discussionmentioning
confidence: 99%
“…Lian et al evaluated 1,965 IPAA procedures and found an AL rate of 5% and fistula formation of 7%. 3 In another large series from Germany with 494 patients, the overall incidence of pouch-related septic complications (PRSCs) was 19.2%. In a 24-year analysis of pediatric patients with FAP undergoing IPAA, Kennedy et al found a low rate of AL or pelvic abscess in their patient cohort (7.4%).…”
Section: Epidemiologymentioning
confidence: 98%
“…Interestingly, they found that functional results at 5 years were better after a leak from a stapled anastomosis compared with an HS anastomosis, specifically with a lower incontinence rate and lower nocturnal seepage rates, likely owing to the height of the anastomosis. 3…”
Section: Sutured Versus Stapled Ileal Pouch-anal Anastomosismentioning
confidence: 99%